Foundation Game Design with HTML5 and JavaScript - van der Spuy, Rex (Apress : Imprint: Apress, 2012)
Foundation Game Design with HTML5 and JavaScript teaches you everything you need to know about how to make video games. If you've never done any programming before and don't know where to start, this book will show you how to make games from start to finish. You'll learn all the latest programming technologies (HTML5, CSS, and JavaScript) to create your games. All written in a fun and friendly style with open-ended projects that encourage you to build your own original games. Foundation Game Design with HTML5 and JavaScript starts by showing you how you can use basic programing to create logic games, adventure games, and create interactive game graphics. Design a game character, learn to control it with the keyboard, mouse, or touch screen interface, and then learn how to use collision detection to build an interactive game world. You'll learn to make maze games, platform jumping games, and fast paced action games that cover all the popular genres of 2D gaming. Create intelligent enemies, use realistic physics, sound effects and music, and learn how to animate game characters. Whether you're creating games for the web or mobile devices, everything you need to get started on a career as a game designer is right here. Focused and friendly introduction to making games with HTML5. Essential programming and graphic design techniques for building games, with each chapter gently building on the skills of preceding chapters. Detailed case studies demonstrating techniques that can be used for making games in a wide variety of genres.